2021
DOI: 10.7759/cureus.19034
|View full text |Cite
|
Sign up to set email alerts
|

Marinacci Anastomosis: A Case Report

Abstract: Marinacci anastomosis or the reverse Martin-Gruber anastomosis is a rare anomalous intercommunication from the ulnar nerve to the median nerve in the forearm. A young lady was involved in a road traffic accident that resulted in the fracture of both forearm bones for which she was treated surgically. A nerve conduction study was performed later on, which incidentally demonstrated findings of this communication. Knowledge of this anastomosis can help prevent misdiagnosis of clinical findings and misinterpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…This rare ulnar-median anomalous communication has mainly been reported as an incidental finding and the majority of patients diagnosed with am MC had noncontributory symptoms (Table 1) [7]. Accordingly, only two studies reported upper extremity neurologic manifestations that resulted in the diagnosis of MC [2,8]. Notably, both of these patients had a previous history of upper extremity trauma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This rare ulnar-median anomalous communication has mainly been reported as an incidental finding and the majority of patients diagnosed with am MC had noncontributory symptoms (Table 1) [7]. Accordingly, only two studies reported upper extremity neurologic manifestations that resulted in the diagnosis of MC [2,8]. Notably, both of these patients had a previous history of upper extremity trauma.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, it is speculated that the prevalence of MC has been underreported. A review of the literature suggests that this normal anatomic variation tends to often occur bilaterally [8,9]. Being aware of the presence of an anomalous nerve communication is of great importance when performing surgery as it increases the risk for iatrogenic nerve damage [2].…”
Section: Discussionmentioning
confidence: 99%
“…The communicating branch contains mainly motor fibers, rarely sensory, as in MGA [31,71]. Hodzic et al [70] observed a communicating branch of 5.2 cm behind the ulnar artery.…”
Section: Median Nervementioning
confidence: 99%